Balmori Associates: Landscape Representation - Javier González-Campaña; Noemie Lafaurie-Debany (Diségno)
The discipline of landscape architecture is undergoing a reinvention, becoming central to shaping public spaces through comprehensive approaches that address equity, social inclusion, the climate crisis and biodiversity and standing as a powerful design tool, fostering dialogue on the evolving relationship between humans and nature. Within this renewal of the field, nowhere has the representation been more scrutinized than in landscape architecture, becoming main topic of the ongoing debate. [read more]